2017
DOI: 10.1007/s00268-017-4137-x
|View full text |Cite
|
Sign up to set email alerts
|

Are American Surgical Residents Prepared for Humanitarian Deployment?: A Comparative Analysis of Resident and Humanitarian Case Logs

Abstract: Background Effective humanitarian surgeons require skills in general surgery, OB/GYN, orthopedics, and urology. With increasing specialization, it is unclear whether US general surgery residents are receiving exposure to these disparate fields. We sought to assess the preparedness of graduating American surgical residents for humanitarian deployment. Methods We retrospectively analyzed cases performed by American College of Graduate Medical Education general surgery graduates from 2009 to 2015 and cases perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…However, targeted subspecialty practitioners were more often requested, notably OB/GYN and Emergency Medicine. This reflects existing literature on surgical caseloads from humanitarian organizations, showing frequent OB/GYN and orthopedic cases [ 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, targeted subspecialty practitioners were more often requested, notably OB/GYN and Emergency Medicine. This reflects existing literature on surgical caseloads from humanitarian organizations, showing frequent OB/GYN and orthopedic cases [ 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…Lin et al . conducted a comparative analysis between the logbooks of general surgical trainees in USA between 2009 and 2015 and the procedures performed by MSF between 2008 and 2012.…”
Section: Contemporary General Surgical Trainingmentioning
confidence: 99%
“…39,40 Non-operative management of penetrating abdominal trauma in patients who meet strict criteria is also gaining popularity. 41 Lin et al 6 conducted a comparative analysis between the logbooks of general surgical trainees in USA between 2009 and 2015 and the procedures performed by MSF between 2008 and 2012. The authors found that the US general surgical trainees had minimal experience in orthopaedic and obstetric surgery, while both featured prominently in the logbooks of MSF surgeons.…”
Section: Contemporary General Surgical Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…New mechanisms for obtaining relevant surgical skills should be developed to better prepare surgical trainees from industrialized countries interested in humanitarian work. 61 As such, knowledge of the surgical skills required to adequately respond to humanitarian emergencies is essential to prepare surgeons and plan for interventions. MSF's review of required surgical skills urgently called for a basic skill set that any aspiring volunteer surgeon needs to be familiar with in resource-limited humanitarian emergency settings, 62 and much of that basic skill set is also the basis for the ICRC War Surgery Seminar.…”
Section: Public Health Emergencies Of International Concern (Pheics)mentioning
confidence: 99%